#TITLE_ALTERNATIVE# - ARIEF RAHMAN (NIM : 12909007); Pembimbing : Dr.rer.nat. Mutiara Rachmat Putri; Dr.rer.nat., MUHAMMAD
Current data analysis in Gaspar and Karimata Strait was done to determine the characteristic and circulation pattern of ocean current. Current data obtained from South China Sea-Indonesia Seas Transport/Exchange (SITE) research observation from October 2011-February 2012 and July-October 2012 by bottom mooring Acoustic Doppler Current Profilers (ADCP). The observation shows that mean current velocity in December 2011, which is the period of the northwest monsoon, in Gaspar Strait is 0,57 m/second at the near surface and has same direction with surface wind. In August 2012, mean current velocity at the surface level is 0,52 m/second in Gaspar Strait and 0,7 m/second in Karimata Strait and has same direction with surface wind that occur in the south east monsoon. At the bottom layer, the current flow to north in Gaspar Strait and to the northwest in Karimata Strait with slow velocity in September 2012. Tidal current in Gaspar and Karimata Strait have a diurnal tidal tipe. The tidal current flow to the north-nothwest in flood period and flow to the south-southeast in ebb period with mean current velocity that occur at spring tide is up to 0,2 m/second. The shallow water effect couses the semi mayor axis of current tidal ellipse decrease with depth but it does not change the direction of ellipse rotation that rotate clockwise in all depth layer. Residual current shows that the current flow to the south-southeast in the nortwest monsoon and flow to the north-northwest in the southeast monsoon. In Gaspar and Karimata Strait, the residual current is bigger than its tidal current.